2011
DOI: 10.2337/dc11-0077
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Lower-Extremity Amputations in People With and Without Diabetes in Spain, 2001–2008

Abstract: OBJECTIVETo examine trends in nontraumatic lower-extremity amputations (LEAs) over an 8-year period in patients with and without diabetes in Spain.RESEARCH DESIGN AND METHODSWe identified all patients who underwent an LEA using national hospital discharge data. Discharges were grouped by diabetes status: type 1 diabetes, type 2 diabetes, and no diabetes. The incidence of discharges attributed to amputations were calculated overall and stratified by diabetes status and year. We calculated length of stay and in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
64
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 22 publications
13
64
0
3
Order By: Relevance
“…Reasons for the high ratio of minor-to-major amputations in Spain may be associated with the performing of more conservative limb-salvage procedures and increasingly more aggressive treatment of peripheral arterial disease in these patients [20]; however, with observational data we are unable to establish whether the drop in Our data show that the male sex is at higher risk for LEAs than females, confirming the data that emerged from previously published studies [4,18,25]. However, although the prevalence of diagnosed diabetes has increased considerably in men, it may not fully explain the increasing male predominance in LEAs [26].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Reasons for the high ratio of minor-to-major amputations in Spain may be associated with the performing of more conservative limb-salvage procedures and increasingly more aggressive treatment of peripheral arterial disease in these patients [20]; however, with observational data we are unable to establish whether the drop in Our data show that the male sex is at higher risk for LEAs than females, confirming the data that emerged from previously published studies [4,18,25]. However, although the prevalence of diagnosed diabetes has increased considerably in men, it may not fully explain the increasing male predominance in LEAs [26].…”
Section: Discussionsupporting
confidence: 83%
“…As the prevalence of diabetes increases, the number of LEAs in people with diabetes will go up [1]. A recent report showed an increase in major and minor amputations in patients with T2DM, while the number of T1DM -related LEAs decreased in Spain between 2001 and 2008 [4]. However, in Europe the principal trend is a reduction in major amputation rates, and in some countries the improvement observed in the incidence of amputation could be related to the implementation of the recommendations published by the International Working Group on the Diabetic Foot or as a benefit of the Multidisciplinary Diabetic Foot Units (MDFU) [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…than DM patients without LEAs. One study conducted in England showed similar findings [8], and a study conducted in Spain detected increases in LEAs among people with Type 2 DM, while decreases in people with Type 1 DM [15]. However, other regions did not have the same experience.…”
Section: Discussionmentioning
confidence: 72%
“…the major: minor ratio, which is important in proper evaluation of improvements KSA: Kingdom of Saudi Arabia * Table 2, ** Table 3, *** Table 4 in care organization and multidisciplinary-centered protocols. 19,20) Similar to developed countries 21) such registries will give opportunities for cross-national learning to improve health system performance. It will also help in assessing the outcomes of newer modalities of treatment.…”
Section: Discussionmentioning
confidence: 99%